PENGARUH PEMBERIAN GIBERELIN DAN PUPUK KALIUM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Nora Katrin; Nurbaiti; Murniati (DINAMIKA PERTANIAN, 2021)
This research aims to find out the interaction effect of gibberellin and potassium fertilizer doses, to examine the effect potassium fertilizer doses on various gibberellin concentrations, gibberellin concentrations on various potassium fertilizer doses, and to find the main effect of gibberellin and potassium fertilizer which is better for growth and the production of shallot plant. The research was conducted at the UPT of the Faculty of Agriculture, Riau University, Pekanbaru, starting from December 2018 to February 2019. The method was experimentally arranged using the completely randomized block design. The main plot was the gibberellin concentrations (0, 100, 200 and 300) ppm. The sub plot was the dose of potassium fertilizer (100 and 200) kg of KCl ha-1. The parameter observed were plant height, total of leaves, diameter of bulbs, total bulbs per clump, fresh weight of bulbs per clump/plot, and dry weight of bulbs. The data were analyzed statistically with anova and Duncan test continued level of 5%. There was interaction effect of gibberellin and potassium fertilizer increased the fresh weight of bulbs. The treatment 100 kg of KCl ha-1 and 200 ppm of gibberellin increased the fresh weight and dry weight of bulbs. The treatment 200 kg of KCl ha-1 and 200 ppm of gibberellin was better to increase the total of leaves and diameter of bulbs. The treatment of gibberellin 200 ppm was better to increase the fresh weight and dry weight of bulbs. The treatment of 200 of KCl ha-1 increased the plant height and total of leaves.